Incidencia del ajedrez como estrategia didáctica en el mejoramiento de la atención de los niños del grado 5b en la clase de matemáticas, de la institución educativa Jorge Isaac, del corregimiento de Santa Elena, municipio de El Cerrito, Valle del Cauca (2018)
Numerous students and young people interested in participating in the national and international exam as Carlos Cuartas, Cristian Rios, Sergio Barrientos, Martha Mateus and Laura Domínguez among others; But nevertheless to achieve this reform it has much to be prepared for, but this is only acquired through the means that the chess player is technically well-founded for the correct attention of the tactics required by the situation of the game, an example that happens very often it is the attention the student must have in front of the mathematics classes; important subject for education and that must be present for the educational benefit of children. In this regard, we must bear in mind that this sport must be taken into account to achieve the expected success of the case. child learning in front of math classes. From the first moment that he starts the practice with the group of children of the educational institution Jorge Isaac; note the lack of attention of the group in front of the math classes and the low performance of the students in front of the grades, where there are the errors that are presented in front of the classes that provoke the neglect of the children in this subject, where could result in the inappropriate learning of students in mathematics. Therefore, upon discovering this deficiency, the following work was planned to improve learning with a methodology established in a qualitative approach that allows me to observe group qualities in front of math classes, with 2 categories such as Attention and Chess. as a didactic strategy for the improvement of attention and for each category of 3 subcategories such as concentration, interest and attitude. In front of the subject one works with a constructivist method, in charge of formulating the necessary ideas to attend the learning process in this subject.